Gender Equality in Decision-Making Positions: The Efficiency Gains - Paola Profeta (Intereconomics, 2017)
Women are under-represented in decision-making positions worldwide. However, gender equality and diversity are recognised to have beneficial effects on organisations, institutions and the overall economy. This article provides evidence that removing the glass ceiling — the invisible barriers which prevent women from reaching upper-level positions — may produce not only more equality but also substantial efficiency gains.
Keywords: 330